The Dynamics of Cultural Capital in the Sekolah Penggerak Program: at SMAN 1 Babakan Madang, Bogor Regency - Annetha Novika Adnan; Elly Malihah; Wilodati (Faculty of Social Science, Universitas Negeri Malang, 2024)
This study explores the dynamic cultural capital through the Sekolah Penggerak Program at SMAN 1 Babakan Madang, Bogor Regency, emphasizing its impact on students' identity and character. The results showed a positive relationship between cultural capital, parental education level, income, and students' academic achievement. In addition, geographical disparities in residence also influenced variations in students' cultural capital. The Sekolah Penggerak Program was implemented to improve the quality of learning through various interventions to improve student performance. Using a qualitative research approach with case study method. The study involved interviews, observations, and documentation. The findings describe changes in students' cultural capital before and after participating in the program. In conclusion, the interaction between students' initial habitus and school structure significantly influences the dynamics of cultural capital, emphasizing the important role of education in creating an inclusive and productive educational environment for students, and underlining the importance of equity and excellence in educational outcomes that are increasingly emphasized in the increasingly competitive and complex global education environment.